Antibiotic de-escalation for bloodstream infections and pneumonia: systematic review and meta-analysis. (December 2016) - Paul, M.; Dickstein, Y.; Raz-Pasteur, A.
Abstract: Antibiotic de-escalation is an appealing strategy in antibiotic stewardship programmes. We aimed to assess its safety and effects using a systematic review and meta-analysis. We included randomized controlled trials (RCTs) and observational studies assessing adults with bacteraemia, microbiologically documented pneumonia or severe sepsis, comparing between antibiotic de-escalation and no de-escalation. De-escalation was defined as changing an initially covering antibiotic regimen to a narrower spectrum regimen based on antibiotic susceptibility testing results within 96 hours. The primary outcome was 30-day all-cause mortality. A search of published articles and conference proceedings was last updated in September 2015. Crude and adjusted ORs with 95% CI were pooled in random-effects meta-analyses. Sixteen observational studies and three RCTs were included. Risk of bias related to confounding was high in the observational studies. De-escalation was associated with fewer deaths in the unadjusted analysis (OR 0.53, 95% CI 0.39–0.73), 19 studies, moderate heterogeneity. In the adjusted analysis there was no significant difference in mortality (adjusted OR 0.83, 95% CI 0.59–1.16), 11 studies, moderate heterogeneity and the RCTs showed non-significant increased mortality with de-escalation (OR 1.73, 95% 0.97–3.06), three trials, no heterogeneity. There was a significant unadjusted association between de-escalation and survival in bacteraemia/severe sepsis (OR 0.45, 95% CI 0.30–0.67) and ventilator-associated pneumonia (OR 0.49, 95% CI 0.26–0.95), but not with other pneumonia (OR 0.97, 95% CI 0.45–2.12). Only two studies reported on the emergence of resistance with inconsistent findings. Observational studies suggest lower mortality with antibiotic susceptibility testing-based de-escalation for bacteraemia, severe sepsis and ventilator-associated pneumonia that was not demonstrated in RCTs.